Failure of platelet function analyser 200 to demonstrate clinical clopidogrel resistance in a patient undergoing intracranial vascular stenting - Bell, Hayden (BMJ Case Rep, 2020)
A patient undergoes intracranial stent insertion for stent-assisted coiling of a basilar tip aneurysm and left middle cerebral artery aneurysm. A flow diverting stent is also placed across an anterior communicating artery aneurysm. Prior to the procedure, the patient takes dual antiplatelet medications, being aspirin and clopidogrel. Because of the concern regarding in-stent thrombus and thromboembolic complications related to intracranial stenting and the high rate of clopidogrel resistance, preoperative platelet function testing (PFT) was undertaken to ensure platelet inhibition. In this case, PFT was performed on a platelet function analyser which demonstrated platelet inhibition. Ten days following the procedure, the patient represented with thromboembolic stroke. Repeat PFT performed with whole blood impedance aggregometry and despite full medication compliance demonstrated clopidogrel resistance. Clopidogrel was then ceased and prasugrel commenced. This case demonstrates the importance of appropriate platelet inhibition in patients with intracranial stents and the controversy surrounding PFT.